“Pseudomonas fluorescens” as an Antagonist to Control Okra Root Rotting Fungi Disease in Plants - Harsha Sharma; Mohd Anul Haq; Ashok Kumar Koshariya; Anil Kumar; Sandeep Rout; Karthikeyan Kaliyaperumal (Journal of Food Quality)
The common bacteria found in fruit and vegetables are Pseudomonas fluorescens which is Germ-negative and is rod-shaped. Pseudomonas fluorescens has been originated from the rhizosphere of Roorkee-grown okra. The presented work involves recognizing and controlling the isolates of Pseudomonas fluorescens. The scope of the proposed work is that the technique used here is a unique strategy to plant protection and control of rotting fungus diseases based on the recognition and management of Pseudomonas fluorescens isolates. Antagonist effect occurs commonly in vegetable and fruit plants. The main goal of this study is to isolate, identify, and evaluate the development of these bacteria which effects on plant growth. In this research work, five isolates have been chosen for further research based on their morphological, biochemical, and physiological characteristics. All five isolates have been identified as Pseudomonas fluorescens from Bergey’s Manual for the determination of bacteriology. Catalase, urease, amylase, and citrate utilization test were all positive in all of the isolates. PFTT4 was identified to be a likely strain for all plant growth promoting exercises such as age of IAA, HCN, ammonia, and phosphate solubilization subsequent to being assessed for their plant development advancing properties. Further, in vitro exploring uncovered that PFTT4 diminished the development of phytopathogens such as Fusarium solani and extraordinarily further developed seed germination just as all development boundaries like shoot and root length. Furthermore, Pseudomonas sp. PFTT4’s plant growth promoting and antifungal activities put forward to it could be there used because of bioinoculant agents for Abelmoschus esculentus.